Quantitative Astimation of the Size of Building Enterprise - Ginevičius, Romualdas (Ekonomika, 1996)
One or the production concentrations directions is the growth of the organization. It is possible to measure the quantity of enterprises, knowing the number of its employees and the active part of the production’s fund. The analysis showed, that today, building production is of high mechanization and automation. Building enterprises’ quantity is measured by the number of employees.